2017
DOI: 10.1124/jpet.117.240614
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminyl Cyclase Inhibitor PQ912 Improves Cognition in Mouse Models of Alzheimer’s Disease—Studies on Relation to Effective Target Occupancy

Abstract: Numerous studies suggest that the majority of amyloid- (A) peptides deposited in Alzheimer's disease (AD) are truncated and post-translationally modified at the N terminus. Among these modified species, pyroglutamyl-A (pE-A, including N3pE-A40/42 and N11pE-A40/42) has been identified as particularly neurotoxic. The N-terminal modification renders the peptide hydrophobic, accelerates formation of oligomers, and reduces degradation by peptidases, leading ultimately to the accumulation of the peptide and progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 48 publications
0
54
0
Order By: Relevance
“…1 . The pGlu-Aβ-seeded Aβ oligomers possess a very high synaptotoxic, neurotoxic and proinflammatory potential in in-vitro and animal models [ 8 , 9 ]. pGlu-Aβ-seeded oligomers strongly suppressed LTP in brain slices, an indicator of synaptic impairment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 . The pGlu-Aβ-seeded Aβ oligomers possess a very high synaptotoxic, neurotoxic and proinflammatory potential in in-vitro and animal models [ 8 , 9 ]. pGlu-Aβ-seeded oligomers strongly suppressed LTP in brain slices, an indicator of synaptic impairment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…pGlu-Aβ-seeded oligomers strongly suppressed LTP in brain slices, an indicator of synaptic impairment [ 8 ]. In a translational study in an AD animal model, PQ912 significantly rescued impaired spatial learning and memory at a dose which achieved between 50 and 70% QC inhibition in the spinal fluid [ 9 ]. pGlu-Aβ has been shown to induce changes in the secondary and tertiary structure of oligomers and these changes most likely are responsible for the increased synaptotoxic propensity of pGlu-Aβ-containing aggregates [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal pGlu3-modification enhances the formation of hydrophobic Aβ oligomers that have been found to be particularly synapto/neurotoxic [34][35][36][37][38] . Blocking the generation of pGlu3-Aβ peptides via glutaminyl cyclase (QC) inhibitors has been shown to attenuate AD-like pathology and to rescue cognitive function in mice 39,40 . A first QC inhibitor, PQ912, has completed early clinical trial in AD patients 41,42 and is currently entering advanced clinical development.…”
mentioning
confidence: 99%
“…Using a different CD47 antibody (B6H12), we confirmed that overall CD47 protein expression and cell surface localization were not decreased upon transduction with sgRNAs targeting QPCTL (Figures 2D, E; Figure S4). We then tested two small molecule inhibitors of QPCTL, SEN177 29 and PQ912 [30][31][32] , to validate that the enzymatic activity of QPCTL is required for the observed loss of CC2C6 binding, but not B6H12 binding (Figures 2D, F, G;…”
mentioning
confidence: 99%